Empowering women through livelihoods orientated agricultural service provision: A consideration of evidence from Southern Africa - A. J. E. Charman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
The paper considers the impact of livelihoods oriented agricultural service provision for smallholder farmers on gender relationships and food security. The paper contents that the democratization and liberalization of agricultural services towards participatory, bottom-up approaches, from the early 1990s has brought favourable gender gains to women. The paper examines the background to this shift in agricultural service provision. The resulting gender gains, we argue, should be seen in terms of Sen's notion of entitlements. We examine evidence of these gains from developments and cases in Malawi and Zambia and draw supporting evidence from Zimbabwe and South Africa Through a range of interventions – initially driven by NGOs and subsequently adopted within public programmes – women have gained entitlements, including new knowledge of crop production, a firm stakeholding in informal markets, access to adaptable and affordable technologies, and a legitimate role in farmer organizational structures. Through their strengthened legal status and organizational position, women have gained better access to finance and loan package. The impact of these gains is especially evident in the significant expansion of those crops in which women have secured entitlements (in terms of labour, trade and production), notably legumes, vegetables and root and tubers. While the growth in the production of these crops has contributed towards more sustainable livelihoods, it has not translated into improved food security. The paper argues that food security in the case countries remains conditional on maize production, a male controlled crop which underpines patrichal power and political patronage. Until women are afforded full entitlement to produce and own maize, the attainment of food security will remain gender contested.
Keywords: Q12; J43; J16; O13; 330; gender empowerment; food security; sustainable livelihoods; rural development